Đặt \(A=x^2+2y^2+2xy+2x+4y-1\)
\(A=\left(x^2+2xy+y^2\right)+\left(y^2+2y\right)+\left(2x+2y\right)-1\)
\(A=\left[\left(x+y\right)^2+2\left(x+y\right)+1\right]+\left(y^2+2y+1\right)-3\)
\(A=\left(x+y+1\right)^2+\left(y+1\right)^2-3\ge-3\)
Dấu "=" xảy ra \(\Leftrightarrow\)\(\hept{\begin{cases}\left(x+y+1\right)^2=0\\\left(y+1\right)^2=0\end{cases}\Leftrightarrow\hept{\begin{cases}x=0\\y=-1\end{cases}}}\)
Vậy GTNN của \(A\) là \(-3\) khi \(x=0\) và \(y=-1\)
Chúc bạn học tốt ~
Đặt \(B=-x^2-2x-y^2-8y-10\)
\(-B=\left(x^2+2x+1\right)+\left(y^2+8y+16\right)-7\)
\(-B=\left(x+1\right)^2+\left(y+4\right)^2-17\ge-17\)
\(B=-\left(x+1\right)^2-\left(y+4\right)^2+17\le17\)
Dấu "=" xảy ra \(\Leftrightarrow\)\(\hept{\begin{cases}-\left(x+1\right)^2=0\\-\left(y+4\right)^2=0\end{cases}\Leftrightarrow\hept{\begin{cases}x=-1\\y=-4\end{cases}}}\)
Vậy GTLN của \(B\) là \(17\) khi \(x=-1\) và \(y=-4\)
Chúc bạn học tốt ~